2003
DOI: 10.1016/s0378-1097(03)00209-x
|View full text |Cite
|
Sign up to set email alerts
|

RNase H overproduction allows the expression of stress-induced genes in the absence of topoisomerase I

Abstract: Induction of stress proteins in response to heat shock was found to be reduced significantly in Escherichia coli with vtopA mutation. RNase H overexpression in the vtopA mutant partially restored the c 32 -dependent induction of stress genes in response to high temperature and ethanol. The presence of overexpressed RNase H also improved the survival rate of the vtopA mutant after high temperature and oxidative challenges. Topoisomerase I is likely required during stress response for preventing accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…These differential effects of acid and alkaline stress indicate important organism-specific differences in responses to environmental challenges and highlight limits in the ability to generalize about adaptive responses to different, yet related, stresses. Another protein found to be upregulated in the presence of alkaline stress was ribonuclease H (RNase H), which is thought to play several roles in DNA replication (Ogawa and Okazaki, 1984), DNA repair (Rydberg and Game, 2002) and RNA transduction (Cheng et al, 2003).…”
Section: Tablementioning
confidence: 99%
“…These differential effects of acid and alkaline stress indicate important organism-specific differences in responses to environmental challenges and highlight limits in the ability to generalize about adaptive responses to different, yet related, stresses. Another protein found to be upregulated in the presence of alkaline stress was ribonuclease H (RNase H), which is thought to play several roles in DNA replication (Ogawa and Okazaki, 1984), DNA repair (Rydberg and Game, 2002) and RNA transduction (Cheng et al, 2003).…”
Section: Tablementioning
confidence: 99%
“…In a study of the E. coli protein-protein interaction network, topoisomerase I was found to interact with H-NS (Butland et al, 2005), suggesting a functional link between the two proteins. We have demonstrated previously that E. coli topoisomerase I function was required for R-loop suppression in the transcription elongation of stress genes during adaptation to high temperature and oxidative stress (Cheng et al, 2003). In this study, it was found that E. coli topoisomerase I played a different role in gene expression for AR that could involve the influence of DNA topology on the action of the positive and negative regulators of transcription.…”
Section: Discussionmentioning
confidence: 66%
“…Overexpression of RNase H in topA mutants including RFM475 has been shown to correct this defect of R-loop formation (Drolet et al, 1995;Hraiky et al, 2000). The overexpression of RNase H from plasmid pSK760 has also been shown to partially alleviate the effect of topA deletion on the survival rate of RFM475 after high temperature and oxidative challenge (Cheng et al, 2003). We therefore compared the survival rates of topA mutants transformed with either pSK760 expressing wild-type RNase H, or pSK762c expressing an inactive RNase H mutant.…”
Section: Overexpression Of Rnase H Does Not Improve the Ar Of Topa Mumentioning
confidence: 99%
“…E. coli topAnull mutants are not viable at low temperatures (Ͻ30°C) (22,35). Mutants with a topA deletion have increased sensitivity to high temperatures (Ͼ50°C) and oxidative challenges because of defects in transcription of stress response genes needed for survival (6,29,30,39).…”
mentioning
confidence: 99%